Tensile and thermal properties of oil palm empty fruit bunch regnerated cellulose biocomposite films using ionic liquid - Nur Liyana Izyan Zailuddin (School of Materials Engineering, University Malaysia Perlis, 2014)
In this study, the OPEFB contents were varied from 1, 2, 3 and 4 wt% and MCC were fixed at 3 wt%. The effect of OPEFB contents and chemical modification using Butylmethacrylate acid (BMA) and Methacrylic acid (MAA) on X-Ray diffraction, tensile properties, morphology study, thermal properties and FTIR of RC biocomposite films were investigated.